Corridor Development in India : Impact on Land Acquisition. - Yadav, Vinita; Kalambe, Rohini Neelkanthrao ([Place of publication not identified] : Routledge India, 2022)
This book discusses the nuances of corridor development in India and its implications on land acquisition and displacement. It explores the complexities of land related conflicts and its socio-economic impacts on peopleś lives. Examining the evolution of a few corridors of national importance like the Mumbai-Nagpur Expressway, Yamuna Expressway, Delhi-Mumbai Industrial Corridor, and Pune-Mumbai Expressway, the volume provides a comprehensive understanding of the dynamics of corridor development and regional growth. The book discusses how policies relating to land acquisition result in political, economic, legal and psychological hardships. The authors, using primary and secondary data, assess the socio-economic implications of land-acquisition on agriculture, employment, environment, demography, and land utilization along the regions touching these corridors. The work further discusses sustainable interventions in land acquisition practices to ensure equity of land and resources for vulnerable communities. The book will be useful for students and researchers of public policy, development studies, economics, urban and regional development studies and sociology. It will also be of interest to academicians, regional planners, and those working in the field of land development, resettlement and rehabilitation.
Preface. Acknowledgements. Abbreviations. 1. Transport Corridor and its Sustainable Development 2. Land Acquisition: Legal and Regulatory Context3. Dynamic Cohesion of Corridor Development and Land Acquisition 4. Economic and Social Development 5. Sustainable Intervention in Land Acquisition and Corridor Development Index.
Keywords: ARCHITECTURE / Urban & Land Use Planning; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; Regional planning -- India; Express highways -- India; Economic development -- India; Industries -- India